2006
DOI: 10.1167/iovs.05-1150
|View full text |Cite
|
Sign up to set email alerts
|

Expression of Collagen-Binding Integrin Receptors in the Mammalian Sclera and Their Regulation during the Development of Myopia

Abstract: The mammalian sclera expresses the major collagen-binding integrin subunits. The alpha1 and beta1 subunit expression was decreased early during the development of myopia, whereas the regulation of alpha2 integrin occurred at a later time point. The differential regulation of alpha1beta1 and alpha2beta1 during the development of myopia may reflect specific roles for these receptors in the scleral extracellular matrix and biomechanical remodeling that accompanies myopic eye growth.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
69
0
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 77 publications
(74 citation statements)
references
References 51 publications
4
69
0
1
Order By: Relevance
“…The recombinant PIIBNP cleaved with thrombin was run in the second lane, showing the migration of the PIIBNP produced by bacteria. The third through fifth lanes show extracts from human developing limbs reacted with antibody to PIIBNP (exons [3][4][5][6][7][8]. The band that migrates at 16.1-kDa is the monomer of PIIBNP, migrating slightly slower than the recombinant form due to hydroxylation of proline residues.…”
Section: Normal Chondrocytes Have Reduced or Undetectable Receptor Inmentioning
confidence: 99%
“…The recombinant PIIBNP cleaved with thrombin was run in the second lane, showing the migration of the PIIBNP produced by bacteria. The third through fifth lanes show extracts from human developing limbs reacted with antibody to PIIBNP (exons [3][4][5][6][7][8]. The band that migrates at 16.1-kDa is the monomer of PIIBNP, migrating slightly slower than the recombinant form due to hydroxylation of proline residues.…”
Section: Normal Chondrocytes Have Reduced or Undetectable Receptor Inmentioning
confidence: 99%
“…The sclera contains a collagen-rich extracellular matrix that undergoes significant biochemical and biomechanical remodeling during the development of myopia (3). Linkage studies of high myopia have identified potential loci MYP1 (Xq28) and MYP3 (12q21-23); these loci are within and/or near the loci of the human genome containing several genes that encode small leucine-rich proteoglycans (SLRP), 3 i.e.…”
mentioning
confidence: 99%
“…Linkage studies of high myopia have identified potential loci MYP1 (Xq28) and MYP3 (12q21-23); these loci are within and/or near the loci of the human genome containing several genes that encode small leucine-rich proteoglycans (SLRP), 3 i.e. biglycan (Xq27ter), decorin (12q21-22), lumican (12q21.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…There are fi ve distinct categories of receptor genes namely CHRM1 to CHRM5 , which encode for fi ve different MR proteins from M1 to M5, each with distinct pharmacological properties. Ciliary body and iris sphincter express all fi ve subtypes of MR with a predominant role for the M3 subtype [138][139][140].…”
Section: Muscarinic Receptorsmentioning
confidence: 99%